Apoptotic Cell Clearance in Drosophila melanogaster - Zheng, Qian; Ma, AiYing; Yuan, Lei; Gao, Ning; Feng, Qi; Franc, Nathalie C.; Xiao, Hui (Frontiers in Immunology, 2017)
The swift clearance of apoptotic cells (efferocytosis) by phagocytes is a critical event during development of all multi-cellular organisms. It is achieved through phagocytosis by professional or amateur phagocytes. Failure in this process can contribute to the development of inflammatory autoimmune or neurodegenerative diseases. Apoptotic cell clearance has been conserved throughout evolution, although many details in its mechanisms remain to be explored. It has been studied in the context of mammalian macrophages, and in the nematode C. elegans, which lacks ‘professional’ phagocytes such as macrophages, but in which other cell types can engulf apoptotic corpses. In Drosophila melanogaster, apoptotic cells are engulfed by macrophages, glial and epithelial cells. Drosophila macrophages perform similar functions to those of mammalian macrophages. They are professional phagocytes that participate in phagocytosis of apoptotic cells and pathogens. Study of apoptotic cell clearance in Drosophila has identified some key elements, like the receptors Croquemort and Draper, promoting Drosophila as a suitable model to genetically dissect this process. In this review, we survey recent works of apoptotic cell clearance pathways in Drosophila, and discuss the physiological outcomes and consequences of this process.